2016
DOI: 10.5433/1679-0359.2016v37n4p2133
|View full text |Cite
|
Sign up to set email alerts
|

Performance, nutrient digestibility, and quantitative carcass traits of lambs fed sunflower seeds and vitamin E

Abstract: The aim of this study was to evaluate performance, nutrient digestibility, and carcass quantitative traits of lambs fed diets with and without sunflower seeds and vitamin E. Thirty-two uncastrated lambs at approximately 60 days of age, with 15 ± 0.2 kg, were housed in individual stalls and slaughtered at 32.0 ± 0.2 kg body weight. Treatments consisted of the following four diets: C = sugarcane + concentrate; CS = sugarcane + concentrate with sunflower seeds; CE = sugarcane + concentrate with 1,000 mg vitamin E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…The low EE digestibility for the control diet is probably because this fraction is more linked to the waxy portions of foods than to the soluble fats of the oilseeds used (YAMAMOTO et al, 2005b), as reported in the literature (ALMEIDA et al, 2016;NUR ATIKAH et al, 2018;FREITAS JR. et al, 2019). The differences of feed intake caused significant changes in feed efficiency of animals fed different diets.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The low EE digestibility for the control diet is probably because this fraction is more linked to the waxy portions of foods than to the soluble fats of the oilseeds used (YAMAMOTO et al, 2005b), as reported in the literature (ALMEIDA et al, 2016;NUR ATIKAH et al, 2018;FREITAS JR. et al, 2019). The differences of feed intake caused significant changes in feed efficiency of animals fed different diets.…”
Section: Discussionmentioning
confidence: 92%
“…Several animal feeds compete in the human food chain, especially corn. Therefore, alternative feeds to corn in diets for ruminants are important to replace traditional feeds and reduce costs (CORTE et al, 2015;ALMEIDA et al, 2016). Oilseed grains, lipid sources, are used in animal diets to replace rapidly fermentable carbohydrates for fattening and milked animals in many countries, without competing with human diets (HENDERSON et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A cana-de-açúcar utilizada foi a variedade forrageira IAC 86-2480 picada em tamanho de partículas de 1,0 cm e fornecida in natura. O concentrado foi composto por grão de milho triturado, farelo de soja, ureia, cloreto de sódio, calcário calcítico, fosfato bicálcico e suplementos vitamínico e mineral, compondo dietas com valores proteicos e energéticos semelhantes (ALMEIDA et al, 2016). Grãos de girassol compuseram as dietas em 8,08% e a vitamina E em 0,1% (ALMEIDA et al, 2016).…”
Section: Methodsunclassified
“…O concentrado foi composto por grão de milho triturado, farelo de soja, ureia, cloreto de sódio, calcário calcítico, fosfato bicálcico e suplementos vitamínico e mineral, compondo dietas com valores proteicos e energéticos semelhantes (ALMEIDA et al, 2016). Grãos de girassol compuseram as dietas em 8,08% e a vitamina E em 0,1% (ALMEIDA et al, 2016). As dietas foram calculadas de acordo com as exigências preconizadas pelo NRC (2007) para cordeiros desmamados com ganhos de peso estimados em 250g/ dia.…”
Section: Methodsunclassified
“…Sugarcane waste is reported to offer various benefits for ruminant animal feed, particularly as a source of fiber or energy (Endo et al 2014), enhancing carcass characteristics (Almeida et al 2016), and improving milk quality (Ferreira et al 2014). Hence, further exploration is needed regarding the utilization of sugarcane and its by-products from sugarcane cultivation, especially its use as sheep feed.…”
Section: Introductionmentioning
confidence: 99%